Use of Patent Applications as a Tool for Technology Development Prospection on the Ethanol Production Chain from Lignocellulosic Biomasses in Brazil - Luiz André Felizardo Silva Schlittler; Adelaide Maria de Souza Antunes; Nei Pereira Junior (Journal of Technology Management & Innovation, 2012)
The growing concerns regarding the future of global energy supplies have encouraged R&D in alternative sources to complement the global energy matrix. Brazil has earned notoriety as one of the largest producers of ethanol and biomass. This has aroused other countries’ interest in Brazil’s capabilities. However, the technologies for converting biomass into ethanol are not sufficiently mature, and have been developed in a decentralized manner. The lignocellulosic ethanol technologies can be divided into the following three groups: pretreatment, enzymes and ethanol production. One of the most efficient methods for mapping such technologies is through patent applications because the applications provide important information on trends in long-term technological development. Among all the patent applications deposited in the Brazilian database, pretreatment technologies were the most exploited followed by enzymes and ethanol production. The large number of documents from USA and European countries efforts the importance of Brazil in this technological scenario.